A high-strength and high-conductivity titanium bronze ultra-thin strip and preparation method thereof

By adding titanium elements to the copper alloy and carrying out solid solution strengthening and multiple rolling treatments, the contradiction between the strength and conductivity of the copper alloy is solved, and the performance of high strength and high conductivity is achieved. At the same time, the preparation process is simplified and production is improved efficiency.

CN116121584BActive Publication Date: 2025-02-25YUNNAN HONGTA SPECIAL COPPER NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310257234.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-16
Publication Date
2025-02-25
Estimated Expiration
2043-03-16

AI Technical Summary

Technical Problem

In the prior art, increasing the strength of copper alloy will lead to a decrease in conductivity, and multiple annealing treatments are required after rolling, which is cumbersome in preparation and has low production efficiency.

Method used

A high-strength, high-conductance titanium bronze extremely thin strip and its preparation method are adopted. By adding alloy element titanium and copper to form solid solution strengthening, and multiple rolling treatments are carried out, including cold rolling, cleaning and degreasing treatment and time-efficiency treatment, eliminating the removal of The process of annealing after rolling.

Benefits of technology

On the basis of ensuring conductive properties, the strength of copper alloy is significantly improved, the preparation process is simplified, the production efficiency is improved, and the movement of dislocations and grain boundaries is prevented through the aging strengthening method, which improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116121584B_ABST
    Figure CN116121584B_ABST
Patent Text Reader

Abstract

The invention provides a high-strength and high-conductivity titanium bronze ultra-thin strip and a preparation process thereof, belonging to the relevant technical field of high-strength and high-conductivity copper alloys. The mass percentage composition of the high-strength and high-conductivity titanium bronze ultra-thin strip is: Ti: 1.8-5.1%, Si content is less than 0.0019%, and the balance is Cu and inevitable impurities. The preparation method comprises melting, homogenization annealing, hot rolling, solution treatment, milling, multiple rolling treatments and post-treatment in sequence. The invention precipitates a large number of uniformly distributed second phase particles through aging treatment, which can prevent the movement of dislocations and grain boundaries to improve the strength. The aging strengthening method has a significant effect, and the conductivity will not be greatly reduced while the strength is improved. During cold rolling, a four-roller rolling mill, a 20-roller rolling mill, and a combined forming rolling mill are used for rolling, which effectively reduces the influence of work hardening on the rolling process, reduces the number of rolling passes as much as possible, and saves the process of annealing after rolling, thereby improving production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field related to high-strength and high-conductivity copper alloys, and relates to a high-strength and high-conductivity titanium bronze ultra-thin strip and a preparation method thereof. Background Art

[0002] Copper and copper alloys have excellent electrical conductivity and occupy an important position in the electrical and electronic industries. However, with the development of science and technology, the requirements for conductive materials are no longer just the single property of conductivity, but high-performance copper alloys with diverse comprehensive properties such as high strength, high conductivity, and high wear resistance. For example, the lead frames of large-scale integrated circuits, commutators of power tools, microwave tubes, and components of aerospace vehicles all require materials to have higher strength while maintaining excellent electrical conductivity. Therefore, everyone is constantly exploring materials with excellent comprehensive physical and mechanical properties - high-strength and high-conductivity copper alloys.

[0003] However, the key problem faced in the research and development of high-strength and high-conductivity copper alloys is the conflicting relationship between strength and conductivity, that is, if the strength of the copper alloy is increased, the conductivity will decrease to some extent. Therefore, how to increase the strength of the copper alloy as much as possible while ensuring excellent conductivity has become an important issue we need to solve.

[0004] After searching, the Chinese patent application number is CN202011109817.4, and the application publication date is February 5, 2021. The name of the invention is: A method for preparing a high-strength and high-conductivity copper alloy Cu-Cr-Si-Ti strip. The process steps of this application are: (1) preparing Cu-Cr-Si-Ti alloy ingots in an industrial frequency cored induction furnace; (2) hot rolling and cold rolling the Cu-Cr-Si-Ti alloy ingots; (3) annealing the cold-rolled ingots; (4) rolling the annealed alloy ingots; (5) annealing the rolled alloy ingots. This application does not perform aging treatment after solid solution of the alloy element Ti, resulting in low strength. At the same time, multiple annealing treatments are required after rolling. The preparation process is still somewhat cumbersome and energy-consuming. Summary of the invention

[0005] In view of this, the present invention provides a high-strength and high-conductivity titanium bronze ultra-thin strip and a preparation method thereof in order to solve the problems in the prior art that while the strength of copper alloy is improved, the conductivity will decrease to a certain extent; multiple annealing treatments are required after rolling, the preparation process is cumbersome and the production efficiency is low.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A high-strength and high-conductivity titanium bronze ultra-thin strip, the mass percentage composition of the high-strength and high-conductivity titanium bronze ultra-thin strip is: Ti:

[0008] 1.8~5.1%, Si: less than 0.0019%, and the balance is Cu and inevitable impurities.

[0009] A method for preparing a high-strength and high-conductivity titanium bronze ultra-thin strip, which comprises, in sequence, melting and casting, homogenizing annealing, hot rolling, solution treatment, milling, multiple rolling treatments and post-treatment; the multiple rolling treatments comprise, in sequence, cold rolling, cleaning and degreasing treatments and aging treatments; in the multiple rolling treatments, the first cold rolling adopts a four-roller rolling mill, the single-pass rolling deformation is 5-25%, the total deformation is 50-95%, and after the first cold rolling, the thickness of the titanium bronze strip is 1.0-7 mm; in the multiple rolling treatments, the intermediate rolling The cold rolling process adopts a 20-roller mill, the working roll diameter is 45-55mm, and the thickness of the titanium bronze strip after cold rolling is 0.05-0.5mm; the last cold rolling in multiple rolling processes adopts a combined forming mill, the working roll diameter is 30-45mm, the single-pass rolling deformation is 15-35%, and the total deformation is 60-99%; after the last cold rolling, the thickness of the titanium bronze strip is 0.005-0.01mm, and the last rolling process does not include aging treatment.

[0010] Furthermore, after the first cold rolling, the tensile strength of the titanium bronze strip is 680-750MPa, the yield strength is 650-710MPa, the conductivity is 4-6%IACS, the Vickers hardness is 200-250HV, and the elongation is 0.4-0.8%; the first aging treatment process is: the insulation temperature is 370-450°C, the insulation time is 1-2.5h, and the protective atmosphere is 99.99% high-purity hydrogen; after the first aging treatment, the tensile strength of the titanium bronze strip is 850-900MPa, the yield strength is 830-890MPa, the conductivity is 10-15%IACS, the Vickers hardness is 290-320HV, and the elongation is 4-7%.

[0011] Furthermore, the intermediate rolling treatment includes two times in the multiple rolling treatments, wherein the single rolling deformation of the second cold rolling is 5-25%, and the total deformation is 45-95%; after the second cold rolling, the thickness of the titanium bronze strip is 0.2-1 mm; after the second cold rolling, the tensile strength of the titanium bronze strip is 940-980 MPa, the yield strength is 900-950 MPa, the conductivity is 8-12% IACS, the Vickers hardness is 295-350 HV, and the elongation is 2-4%; the second aging treatment process is: the holding temperature is 350-450°C, and the holding time is 15-45 m in, the protective atmosphere is 99.99% high-purity hydrogen; after the second aging treatment, the tensile strength of the titanium bronze strip is 950-1000MPa, the yield strength is 930-970MPa, the conductivity is 10-15%IACS, the Vickers hardness is 310-350HV, and the elongation is 5-8%; the single-pass rolling deformation of the third cold rolling is 10-35%, and the total deformation is 50-98%; the third aging treatment process is: the holding temperature is 350-400℃, the holding time is 3-20min, and the protective atmosphere is 99.99% high-purity hydrogen.

[0012] Furthermore, the second rolling treatment also includes a trimming treatment after the second aging treatment, which requires cutting off the tiny edge cracks in the second cold rolling process in preparation for the third cold rolling, and the trimming width is 0.5 to 5 mm.

[0013] Furthermore, after the last cold rolling, the titanium bronze strip has a tensile strength of 1000-1150 MPa, a yield strength of 980-1050 MPa, a conductivity of 14-16% IACS, a Vickers hardness of 320-360 HV, and an elongation of 2-5%.

[0014] Furthermore, the thickness of the ingot after melting and casting is 30 to 200 mm.

[0015] Furthermore, the homogenization annealing temperature is 800-870°C, and the time is 1.5-4h; the protective atmosphere is 99.99% high-purity hydrogen, and the ingot after homogenization annealing is subjected to reversible hot rolling, and the start rolling temperature is 800-830°C; the deformation amount per pass is 10-35%, and the total deformation amount of hot rolling is 80-95%; the final rolling temperature is 630-720°C, and after the final rolling, ultra-fast laminar cooling is performed, and rapid cooling is performed at a cooling rate of ≥150°C / s, and the final hot rolling thickness is 3-15mm.

[0016] Furthermore, the solution treatment temperature is 850-960°C, the time is 20-70 minutes, the quenching medium is water, the water temperature is 15-28°C, and the cooling rate is ≥90°C / s. The titanium bronze strip after solution treatment has a tensile strength of 380-420MPa, a yield strength of 290-320MPa, a conductivity of 5-7%IACS, a Vickers hardness of 150-180HV, and an elongation of 10-18%.

[0017] Furthermore, post-processing includes bending and straightening, slitting and packaging.

[0018] The beneficial effects of the present invention are:

[0019] 1. The high-strength and high-conductivity titanium bronze ultra-thin strip and its preparation method disclosed in the present invention form solid solution strengthening by adding alloy elements titanium and copper. Since the solid solubility is extremely small at room temperature, after aging treatment, a uniformly distributed second phase is precipitated in the copper matrix. The presence of a large number of second phase particles can prevent the movement of dislocations and grain boundaries to improve the strength; at the same time, the supersaturated solid solution is precipitated to continuously purify the matrix, and the conductivity of the alloy is continuously improved; the aging strengthening method has a significant effect, which can improve the strength without significantly reducing the conductivity.

[0020] 2. The high-strength and high-conductivity titanium bronze ultra-thin strip and its preparation method disclosed in the present invention adopt a four-roll mill, a 20-roll mill, and a combined forming mill to perform hot rolling and cold rolling on the titanium bronze material, respectively, and reasonably distribute the deformation amount of each cold rolling pass, which effectively reduces the influence of work hardening on the rolling process and reduces the number of rolling passes; the process of annealing after rolling is omitted, thereby improving production efficiency.

[0021] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0023] Figure 1 The present invention is a flow chart of the ultra-thin high-strength and high-conductivity titanium bronze strip and its preparation method. DETAILED DESCRIPTION

[0024] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0025] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.

[0026] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "front", "rear", etc. indicate the orientation or position relationship, they are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as limiting the present invention. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0027] like Figure 1 The high-strength and high-conductivity titanium bronze ultra-thin strip and its preparation method include the following steps:

[0028] In the first step, titanium bronze having a composition of Ti: 3.38%, Si: less than 0.0019%, and the balance of Cu and inevitable impurities is melted and cast into a 30 mm copper ingot.

[0029] In the second step, the copper ingot is subjected to homogenization annealing at 820°C for three hours in a protective atmosphere of 99.9% high-purity nitrogen.

[0030] In the third step, the ingot after homogenization annealing is reversibly hot rolled, with the starting rolling temperature of 820°C, the pass deformation rate of 12%-30%, the total hot rolling deformation of 89.8%, the final rolling temperature of 630°C, and ultra-fast laminar cooling after final rolling, with rapid cooling at a cooling rate of 180°C / s, and the final hot rolling thickness of 3.06mm.

[0031] Table 1 Hot rolling process table:

[0032] Number of passes Entrance thickness / mm Export thickness / mm Pass reduction / mm Pass reduction rate / % 1 30.00 21.00 0.29 30 2 21.00 15.12 5.88 28 3 15.12 11.19 3.93 26 4 11.19 8.50 2.69 24 5 8.50 6.63 1.87 22 6 6.63 5.31 1.33 20 7 5.31 4.24 1.06 20 8 4.24 3.48 0.76 18 9 3.48 3.06 0.42 12

[0033] The fourth step is solution treatment at a temperature of 900°C for 60 min, quenching medium is water, water temperature is 20°C, and cooling rate is 110°C / s.

[0034] The fifth step is to mill the titanium bronze sheet to make the surface smooth and have a metallic color.

[0035] In the sixth step, a four-roll rolling mill is used for the first cold rolling, and the deformation of the first cold rolling single pass is 9-22%, and the total deformation is 58%; after the first cold rolling, the thickness of the titanium bronze strip is 1.27 mm, and the tensile strength of the titanium bronze strip after one cold rolling is 680-750 MPa, the yield strength is 650-710 MPa, the conductivity is 4-6% IACS, the Vickers hardness is 200-250 HV, and the elongation is 0.4-0.8%.

[0036] Table 2 First cold rolling process table:

[0037] Number of passes Entrance thickness / mm Export thickness / mm Pass reduction / mm Pass reduction rate / % 1 3.06 2.39 0.67 22 2 2.39 1.91 0.48 20 3 1.91 1.61 0.31 16 4 1.61 1.40 0.21 13 5 1.40 1.27 0.13 9

[0038] The seventh step is to use alkaline solution to carry out the first cleaning and degreasing treatment of the titanium bronze plate.

[0039] In the eighth step, the first aging treatment process is: the holding temperature is 450°C, the holding time is 2h, the protective atmosphere is 99.99% high-purity hydrogen, and after the first aging treatment, the tensile strength of the titanium bronze strip is 850-900MPa, the yield strength is 830-890MPa, the conductivity is 10-15%IACS, the Vickers hardness is 290-320HV, and the elongation is 4-7%.

[0040] In the ninth step, the second cold rolling adopts a 20-roll mill, the working roll diameter is 45-55mm, the single-pass rolling deformation is 8-23%, and the total deformation is 76%; after the second cold rolling, the thickness of the titanium bronze strip is 0.3mm, the tensile strength of the titanium bronze strip after the second cold rolling is 940-980MPa, the yield strength is 900-950MPa, the conductivity is 8-12%IACS, the Vickers hardness is 295-350HV, and the elongation is 2-4%.

[0041] Table 3 Second cold rolling process table:

[0042] Number of passes Entrance thickness / mm Export thickness / mm Pass reduction / mm Pass reduction rate / % 1 1.27 0.98 0.29 23 2 0.98 0.78 0.20 20 3 0.78 0.64 0.14 18 4 0.64 0.54 0.10 16 5 0.64 0.46 0.08 15 6 0.46 0.40 0.06 13 7 0.40 0.35 0.04 11 8 0.35 0.32 0.03 9 9 0.32 0.30 0.03 8

[0043] The tenth step is to use alkali solution to clean and degrease the titanium bronze plate for the second time.

[0044] In the eleventh step, the second aging treatment process is: the holding temperature is 450° C., the holding time is 30 minutes, the protective atmosphere is 99.99% high-purity hydrogen, and after the second aging treatment, the tensile strength of the titanium bronze strip is 950-1000 MPa, the yield strength is 930-970 MPa, the conductivity is 10-15% IACS, the Vickers hardness is 310-350 HV, and the elongation is 5-8%.

[0045] In the twelfth step, the titanium bronze sheet is trimmed with a trimming width of 1 mm.

[0046] In the thirteenth step, the third cold rolling adopts a 20-roll rolling mill, the working roll diameter is 45-55mm, the single-pass rolling deformation is 11-30%, and the total deformation is 77%; after the third cold rolling, the thickness of the titanium bronze strip is 0.07mm.

[0047] Table 4 The third cold rolling process table:

[0048] Number of passes Entrance thickness / mm Export thickness / mm Pass reduction / mm Pass reduction rate / % 1 0.30 0.21 0.09 30 2 0.21 0.16 0.05 26 3 0.16 0.13 0.03 20 4 0.13 0.11 0.02 17 5 0.11 0.09 0.02 15 6 0.09 0.08 0.01 13 7 0.08 0.07 0.01 11

[0049] In the fourteenth step, the titanium bronze plate is cleaned and degreased for the third time with alkaline solution.

[0050] Step 15: The third aging treatment process is as follows: the insulation temperature is 400° C., the insulation time is 15 min, and the protective atmosphere is 99.99% high-purity hydrogen.

[0051] In the sixteenth step, the fourth cold rolling adopts a combined forming rolling mill, the working roll diameter is 30-45 mm, the single-pass rolling deformation is 20-35%, and the total deformation is 86%; after the fourth cold rolling, the thickness of the titanium bronze strip is 0.01 mm, the tensile strength of the titanium bronze strip after the fourth cold rolling is 1000-1150 MPa, the yield strength is 980-1050 MPa, the conductivity is 14-16% IACS, the Vickers hardness is 320-360 HV, and the elongation is 2-5%.

[0052] Table 5 The fourth cold rolling process table:

[0053] Number of passes Entrance thickness / mm Export thickness / mm Pass reduction / mm Pass reduction rate / % 1 0.07 0.05 0.02 35 2 0.05 0.03 0.02 30 3 0.03 0.02 0.01 27 4 0.02 0.015 0.005 25 5 0.015 0.012 0.003 23 6 0.012 0.01 0.002 20

[0054] Step 17: Use alkali solution to clean and degrease the titanium bronze plate for the fourth time.

[0055] In the eighteenth step, the titanium bronze ultra-thin strip is subjected to stretching, bending and straightening treatment.

[0056] The nineteenth step is to cut the titanium bronze ultra-thin strip.

[0057] The twentieth step is to package the cut titanium bronze ultra-thin strips.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing an ultra-thin high-strength and high-conductivity titanium bronze strip, characterized in that: The mass percentage composition of the high-strength and high-conductivity titanium bronze ultra-thin strip is: Ti: 1.8-5.1%, Si: less than 0.0019%, and the balance is Cu and unavoidable impurities; The preparation method comprises, in sequence, melting and casting, homogenizing annealing, hot rolling, solution treatment, milling, multiple rolling treatments and post-treatment; the multiple rolling treatments comprise, in sequence, cold rolling, cleaning and degreasing treatments and aging treatments; in the multiple rolling treatments, the first cold rolling adopts a four-roller mill, the deformation of a single rolling pass is 5-25%, the total deformation is 50-95%, and the thickness of the titanium bronze strip is 1.0-7 mm after the first cold rolling; in the multiple rolling treatments, the cold rolling of the intermediate rolling treatment adopts a 20-roller mill, the working roll diameter is 45-55 mm, and the thickness of the titanium bronze strip after cold rolling is 0.05-0.5 mm; in the multiple rolling treatments, the last cold rolling adopts a combined forming mill, the working roll diameter is 30-45 mm, the deformation of a single rolling pass is 15-35%, and the total deformation is 60-99%; after the last cold rolling, the thickness of the titanium bronze strip is 0.005-0.01 mm, and the last rolling treatment does not include aging treatment; After the first cold rolling, the tensile strength of the titanium bronze strip is 680-750MPa, the yield strength is 650-710MPa, the conductivity is 4-6%IACS, the Vickers hardness is 200-250HV, and the elongation is 0.4-0.8%; the first aging treatment process is: the holding temperature is 370-450°C, the holding time is 1-2.5h, and the protective atmosphere is 99.99% high-purity hydrogen; after the first aging treatment, the tensile strength of the titanium bronze strip is 850-900MPa, the yield strength is 830-890MPa, the conductivity is 10-15%IACS, the Vickers hardness is 290-320HV, and the elongation is 4-7%; The intermediate rolling treatment includes two times in the multiple rolling treatments, wherein the single rolling deformation of the second cold rolling is 5-25%, and the total deformation is 45-95%; after the second cold rolling, the thickness of the titanium bronze strip is 0.2-1 mm; after the second cold rolling, the tensile strength of the titanium bronze strip is 940-980 MPa, the yield strength is 900-950 MPa, the conductivity is 8-12% IACS, the Vickers hardness is 295-350 HV, and the elongation is 2-4%; the second aging treatment process is: the holding temperature is 350-450°C, and the holding time is 15-45 minutes. n, the protective atmosphere is 99.99% high-purity hydrogen; after the second aging treatment, the tensile strength of the titanium bronze strip is 950~1000MPa, the yield strength is 930~970MPa, the conductivity is 10~15%IACS, the Vickers hardness is 310~350HV, and the elongation is 5~8%; the single-pass rolling deformation of the third cold rolling is 10~35%, and the total deformation is 50~98%; the third aging treatment process is: the holding temperature is 350~400℃, the holding time is 3~20min, and the protective atmosphere is 99.99% high-purity hydrogen; After the last cold rolling, the titanium bronze strip has a tensile strength of 1000-1150 MPa, a yield strength of 980-1050 MPa, a conductivity of 14-16% IACS, a Vickers hardness of 320-360 HV, and an elongation of 2-5%; The ingot after homogenization annealing is subjected to reversible hot rolling, the starting rolling temperature is 800-830°C; the deformation amount per pass is 10-35%, and the total deformation amount of hot rolling is 80-95%; the final rolling temperature is 630-720°C, and after the final rolling, it is subjected to ultra-fast laminar cooling, and the cooling rate is ≥150°C / s for rapid cooling, and the final hot rolling thickness is 3-15mm; Post-processing includes bending and straightening, slitting and packaging.

2. The method for preparing the ultra-thin high-strength and high-conductivity titanium bronze strip according to claim 1, characterized in that: After the second aging treatment, edge trimming is performed to cut off tiny edge cracks in the second cold rolling process in preparation for the third cold rolling, and the edge trimming width is 0.5-5 mm.

3. The method for preparing the ultra-thin high-strength and high-conductivity titanium bronze strip according to claim 1, characterized in that: The thickness of the ingot after melting and casting is 30-200 mm.

4. The method for preparing the ultra-thin high-strength and high-conductivity titanium bronze strip according to claim 1, characterized in that: The homogenization annealing temperature is 800-870° C., the time is 1.5-4 hours, and the protective atmosphere is high-purity hydrogen with a purity of 99.99%.

5. The method for preparing the ultra-thin high-strength and high-conductivity titanium bronze strip according to claim 1, characterized in that: The solution treatment temperature is 850-960°C, the time is 20-70 min, the quenching medium is water, the water temperature is 15-28°C, the cooling rate is ≥90°C / s, and the titanium bronze strip after the solution treatment has a tensile strength of 380-420 MPa, a yield strength of 290-320 MPa, a conductivity of 5-7% IACS, a Vickers hardness of 150-180 HV, and an elongation of 10-18%.

Citation Information

Patent Citations

  • Preparation method of Cu-Cr-Si-Ti copper alloy plate strip

    CN112322917A

  • Cu-Ti based copper alloy sheet material and method for producing the same, and electric current carrying component

    CN104073678A

  • Preparation method of C19400 copper alloy lead frame material

    CN115058670A

  • Titanium copper, method for producing titanium copper and electronic component

    EP3643798A1

  • High-strength copper titanium plate and production method therefor

    WO2011118400A1